DEVIANCE REFLECTED IN AGATHA CHRISTIE’S CROOKED HOUSE - Sumual, Trivosa; Mogea, Tini; Posumah, Jenie (SoCul: International Journal of Research in Social Cultural Issues, 2023)
The aim of this research is to reveal about the deviance of Josephine and its impact that reflected in Agatha Christie’s Crooked House. This research is classified as a qualitative research because the data are taken only in the form of words as well as the quotations. The data sources are taken from the novel itself and supported by other books, dictionary, journals and other references from the internet as the secondary sources. In term of the analysis, the researchers use psychological approach because it is very close with human life, such as feelings, thoughts, and desires. The result of this study shows that there are acts of deviance done by Josephine and it has big impacts. Josephine is planned and killed her family members; she is even willing to hurt herself as an alibi. It happens because of the id of Josephine, the desires to take revenge without thinking about the consequences and the relationship between the perpetrator and the victims that should be satisfied. The impacts of the deviance Josephine done was the left people are living in fear and afraid of being the next target. It is ruining the whole family and also it will effect to their mental health.